1997
DOI: 10.1007/bf02495394
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence of oxygen-free acetone solutions of dimethyldioxirane

Abstract: The decomposition of dimethyldioxirane (1) in oxygen-free acetone solutions (46 ~ is accompanied by chemiluminescence (CL) in the visible spectral region. The emitter of CL is triplet-excited methyl acetate (2"('I')). For the decomposition of solutions of I in acetone and deuterated dimethyldioxirane in acetone-D 6 the decay of CL follows the first-order kinetics, and the kinetic isotope effect is observed. Two mechanisms of the formation of 2*(T) are discussed: ta) chain-radical process and (b) isomerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…The first component of Eqn (23) reflects the consumption of compound 7b in the reaction with the acetonyl radical, while the second one describes the contribution of reaction (13) to the total rate of DMDO decomposition. This differential equation is readily transformed into an analytical expression which appears as: 57,66 ln…”
Section: Dioxiranesmentioning
confidence: 99%
“…The first component of Eqn (23) reflects the consumption of compound 7b in the reaction with the acetonyl radical, while the second one describes the contribution of reaction (13) to the total rate of DMDO decomposition. This differential equation is readily transformed into an analytical expression which appears as: 57,66 ln…”
Section: Dioxiranesmentioning
confidence: 99%
“…Thus, it was found that decomposition of dimethyldioxirane (DMD) in an oxygen-free acetone solution was accompanied by light emission. 5 The same phenomenon was observed upon interaction of dioxiranes with tris(bipyridine)ruthenium(II) [Ru(bipy) 3 ] 6 and some aromatic hydrocarbons. 2,7 In addition, dioxirane as intermediate has been postulated as a source of chemiluminescence in a number of chemical 8,9 and biochemical 10 systems.…”
mentioning
confidence: 55%
“…ketones: oxygen-free acetone solutions. 5 Obviously, this is associated with the favourable conditions for chemiluminescence on a sorbent surface (for example, the absence of quenching by solvent and different impurities in solution). The other reason obviously lies in the mechanism of DMD decomposition itself.…”
mentioning
confidence: 99%
See 2 more Smart Citations